2018
DOI: 10.1186/s12886-018-0821-3
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative proteomics analysis of vitreous body from type 2 diabetic patients with proliferative diabetic retinopathy

Abstract: BackgroundTo compare the abundance of vitreous proteins between the patients with proliferative diabetic retinopathy (PDR) and idiopathic macular hole (IMH).MethodsIn this study, we performed mass spectrometry-based label-free quantitative proteomics analysis of vitreous samples from type 2 diabetic patients with PDR (n = 9) and IMH subjects (n = 9) and identified the abundance of 610 proteins.ResultsOut of 610 proteins, 64 proteins (Group A) were unique to PDR patients, while 212 proteins (Group B) could be i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 42 publications
1
22
0
Order By: Relevance
“…These included deposition of C3d and MAC complex in the choriocapillaries of DR eyes and reduced level of glycosylphosphatidyl inositol-anchored inhibitors of complements such as CD55 and CD59 in the walls of retinal vessels of DR eyes, suggesting the role of the complement pathway in DR (27,28), although it is as yet unclear if this is a cause or an effect of prolonged diabetic insult. Though the vitreous proteome studies have detected several complement proteins such as C3, CFI, CFB, C4A, C4B, C2, C4BPA, CFD, and CFH in PDR subjects (29)(30)(31)(32), their expression levels are highly variable among different studies and do not explain their exact involvement in DR pathology as observed earlier in ROP and AMD. Also, the complement genes do not show any genetic association with the risk of DR as observed in AMD and ROP.…”
Section: Introductionmentioning
confidence: 90%
“…These included deposition of C3d and MAC complex in the choriocapillaries of DR eyes and reduced level of glycosylphosphatidyl inositol-anchored inhibitors of complements such as CD55 and CD59 in the walls of retinal vessels of DR eyes, suggesting the role of the complement pathway in DR (27,28), although it is as yet unclear if this is a cause or an effect of prolonged diabetic insult. Though the vitreous proteome studies have detected several complement proteins such as C3, CFI, CFB, C4A, C4B, C2, C4BPA, CFD, and CFH in PDR subjects (29)(30)(31)(32), their expression levels are highly variable among different studies and do not explain their exact involvement in DR pathology as observed earlier in ROP and AMD. Also, the complement genes do not show any genetic association with the risk of DR as observed in AMD and ROP.…”
Section: Introductionmentioning
confidence: 90%
“…Therefore, timely expression of Kir 4.1 channels in Müller cells is necessary in the uptake of K + released by neurons in response to light and in siphoning these K + out to the vitreous and vasculature 45. We speculate that the effects of altered diurnal rhythm of Kir4.1 channels are multitude the Müller cells may remain10 consistently swollen throughout the course of diabetes resulting in an increase in oxidative stress and arachidonic acid metabolism; decreased light exposure (e.g., cataract) may lead to a decrease in potassium clearance in the vitreous; finally, change in vitreal composition in diabetes46,47 may independently affect the K + homeostasis and normal retinal function, contributing together to the pathogenesis of DR. Our study certainly paves a way for pursuing these possible pathogenic mechanisms of DR in future.…”
Section: Discussionmentioning
confidence: 93%
“…A comprehensive study done by Garcia et al , identified a significant increase in 42kDa fragment of C3 and CFB in PDR vitreous and found it to correlate with the mRNA expression in diabetic retina [22]. Additionally, various vitreous proteome studies in DR also identified the predominant deposition of complement proteins in PDR vitreous [20, 21, 26, 27] though exactly how complements are involved in PDR pathogenesis was not explored. Thus, here for the first time, we attempted a systematic evaluation of both alternative and classical pathwayof complement activation in PDR pathogenesis by analysing proteins of these two pathways in serum as well as in vitreous humor.…”
Section: Discussionmentioning
confidence: 99%